Über ein involutorisches strahlenkomplexepaar - Grincevičius, K. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:К. Гринцевичюс. Об инволютивной паре комплексовK. Grincevičius. Apie involiucinį kompleksų dvejetą